2003
DOI: 10.1016/s0022-5223(03)00018-7
|View full text |Cite
|
Sign up to set email alerts
|

Transit time flow measurement in on-pump and off-pump coronary artery surgery

Abstract: Evaluation of transit time flow measurement is valuable in determining coronary graft patency after coronary artery bypass with cardiopulmonary bypass and coronary artery bypass without cardiopulmonary bypass. Decreased troponin I release suggests a myocardial benefit of coronary artery bypass without cardiopulmonary bypass compared to coronary artery bypass with cardiopulmonary bypass, although the intraoperative transit time flow measurement flow measurements are markedly lower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 17 publications
5
30
0
Order By: Relevance
“…The values of P w (mean P w = 38.3 ± 5.5 mmHg), Q LADg (mean Q LADg = 31.2 ± 10.1 mL/min), and Q LCXg (mean Q LCXg = 31.7 ± 10.1 mL/min) determined by simulations for the 7 patients were in acceptable agreement with the clinical measured values presented in Table 2. They are also in agreement with values reported in the literature: the off-pump flow rate in the left internal mammary artery is given by Kjaergard et al 12 as 34.4 ± 2.9 mL/ min and as 27.22 ± 15.55 mL/min by Schmitz et al 22 The flow rates across the stenoses Q LAD1 (mean Q LAD1 = 4.1 ± 1.4 mL/min) and Q LCX1 (mean Q LCX1 = 7.0 ± 2.2 mL/min) become small due to the presence of the left bypasses. However, the flow in RCA capillaries Q RCAc is not improved by the presence of the left grafts, as compared to the case (0G) (Q RCAc (2G) = 24.1 ± 8.1 mL/ min vs. Q RCAc (0G) = 24.4 ± 9.1 mL/min).…”
Section: Case (2g): Left Coronary Grafts Working and Right Graft Clampedsupporting
confidence: 91%
See 2 more Smart Citations
“…The values of P w (mean P w = 38.3 ± 5.5 mmHg), Q LADg (mean Q LADg = 31.2 ± 10.1 mL/min), and Q LCXg (mean Q LCXg = 31.7 ± 10.1 mL/min) determined by simulations for the 7 patients were in acceptable agreement with the clinical measured values presented in Table 2. They are also in agreement with values reported in the literature: the off-pump flow rate in the left internal mammary artery is given by Kjaergard et al 12 as 34.4 ± 2.9 mL/ min and as 27.22 ± 15.55 mL/min by Schmitz et al 22 The flow rates across the stenoses Q LAD1 (mean Q LAD1 = 4.1 ± 1.4 mL/min) and Q LCX1 (mean Q LCX1 = 7.0 ± 2.2 mL/min) become small due to the presence of the left bypasses. However, the flow in RCA capillaries Q RCAc is not improved by the presence of the left grafts, as compared to the case (0G) (Q RCAc (2G) = 24.1 ± 8.1 mL/ min vs. Q RCAc (0G) = 24.4 ± 9.1 mL/min).…”
Section: Case (2g): Left Coronary Grafts Working and Right Graft Clampedsupporting
confidence: 91%
“…This is an approximation, since these values probably vary slightly with the revascularization state of the patients (0G, 1G, 2G) due to the surgical procedure. 22,25 However, due to the low pressure drop in the grafts, the increase of flow rate in a capillary region due to the presence of a graft is associated with an increase of the corresponding P i pressure. Consequently, from a mechanical point of view, the ratios…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schmitz et al [20] reported graft flow values of LITA-ADA in the off-pump group, with an average of 27.92 ml / min, values which are smaller than those observed in the on-pump group, in which the average value was 40.25 ± 22.92 ml / min. This difference was attributed to secondary coronary vasodilation to acidosis during EC and less need for use of noradrenaline in this group.…”
Section: Discussionmentioning
confidence: 89%
“…7,9,22,35,36 The results of clinical trials by Desai et al showed that the sensitivity and specifi city of TTFM in detecting greater than 50% stenosis or occlusion were 25% and 98.4%, respectively. 35 ICG imaging with those of TTFM, but this comparison may not be useful.…”
Section: Usability Of the Icg Imaging System In Cabgmentioning
confidence: 99%